2022
DOI: 10.1177/09603271211063165
|View full text |Cite
|
Sign up to set email alerts
|

Role of the AMPK signalling pathway in the aetiopathogenesis of ocular diseases

Abstract: Background AMP-activated protein kinase (AMPK) plays a precise role as a master regulator of cellular energy homeostasis. AMPK is activated in response to the signalling cues that exhaust cellular ATP levels such as hypoxia, ischaemia, glucose depletion and heat shock. As a central regulator of both lipid and glucose metabolism, AMPK is considered to be a potential therapeutic target for the treatment of various diseases, including eye disorders. Objective To review all the shreds of evidence concerning the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 270 publications
(314 reference statements)
0
2
0
Order By: Relevance
“…AMPK pathway also regulates metabolism and protects cells from pathogenic alterations in DR ( 29 ). It has been reported that the AMPK signaling pathway is involved in the etiopathogenesis of many ocular diseases, including DR ( 30 ). Song et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK pathway also regulates metabolism and protects cells from pathogenic alterations in DR ( 29 ). It has been reported that the AMPK signaling pathway is involved in the etiopathogenesis of many ocular diseases, including DR ( 30 ). Song et al.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK pathway also regulates metabolism and protects cells from pathogenic alterations in DR (29). It has been reported that the AMPK signaling pathway is involved in the etiopathogenesis of many ocular diseases, including DR (30). Song et al demonstrated that stimulation of AMPK signaling pathway attenuate diabetes-induced photoreceptor degeneration through regulation of autophagy and mitochondrial function (31).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, pharmacological activation of AMPK by AICAR treatment has been shown to downregulate cytoskeletal and ECM proteins in primary human trabecular meshwork cells by phosphorylating RhoA at Ser188 [159]. In addition, ocular hypertension, which is characterized by increased intraocular pressure, also triggers AMPK activation and contributes to RGC loss [160]. Furthermore, the spatiotemporal expression of MAPKs in the retina and optic nerve has also been implicated in the pathogenesis of glaucoma with increased intraocular pressure.…”
Section: Glaucomamentioning
confidence: 99%